Analysis of Creative Thinking Ability and Learning Outcomes Through the Treffinger Learning Model - Kusmiyati, Kusmiyati; Merta, I Wayan (Jurnal Pijar Mipa, 2025)
This study aims to describe creative thinking skills and learning outcomes through learning with the Treffinger model. The subjects of this study were Biology Education students who took the Animal Structure course in the odd semester of the 2024/2025 academic year, with a total of 24 students. Creative thinking data were collected using instruments with a Likert scale, while tests collected learning outcomes. The collected data were analyzed qualitatively into five categories. The results of the analysis of creative thinking skills showed students with the very good category as many as 11 people (46%) and the good category 13 people (54%). Students with a very good category had the most fluency indicator of 19 people, while those with the good category had the most elaboration indicator for 16 students. Learning outcomes are more in the good ranking of 16 people than the very good category (8 people). Through learning the Treffinger model, creative thinking ability, and learning outcomes of animal structure, students vary in the categories of good and very good.